Faktor Media terhadap Kejadian Bullying pada Anak Usia Sekolah - Selvia Novitasari; Ferasinta Ferasinta; Padila Padila (Jurnal Kesmas Asclepius, 2023)
This study aims to determine the relationship between media factors and the incidence of bullying in school-age children. The research method used is quantitative, using an explanatory survey method with a cross-sectional approach. The results showed that the media factor chi-square test obtained a p-value of 0.001 < (α = 0.05). In conclusion, there is a relationship between media factors and the incidence of bullying in school-age children. Keywords: School Age Children, Bullying, Media